The Effect of Prenatal Ethanol Exposure on Volume of Pars Distalis of Pituitary Gland in The Rat Pups - Rashid, Nadia; Akhtar, Lubna; Islam, Sobia; Minhas, Ruqqia Shafi; Adnan, Naushin (ADVANCES IN BASIC MEDICAL SCIENCES, 2021)
Background: To determine the effect of prenatal ethanol exposure (PEE) on the volume of pars distalis of pituitary gland in the male rat pups. Methodology: For breeding, sixteen female Sprague Dawley rats were obtained by random sampling method. They were allowed mating with four male rats and divided into control group A and experimental groups B. Experimental group (B) rats were injected intraperitoneally with 4.44ml/kg ethanol while control group (A) with same amount of normal saline from gestational day 10 (GD 10) to gestational day 18 (GD 18). Both groups were given standard laboratory conditions for normal completion of their gestation and were allowed to deliver spontaneously. Only male pups were included in this study. Pups were reared till fifth day postnatally. Pituitary glands were removed and stained with Periodic acid Schiff-orange G (PAS-OG) stain for histological study. Area of pars distalis of pituitary gland was measured using image-J. The area was multiplied by thickness of the section to get the volume of pars distalis of pituitary gland. Results: Mean volume of pars distalis of pituitary gland was reduced significantly in experimental group (0.085± 0.010 mm3) as compared to control group (0.122±0.005 mm3) (p- value 0.002). Conclusion: Prenatal ethanol exposure causes significant reduction in volume of pars distalis of pituitary gland in the male rat pups. Key Words: Ethanol, Volume, Pars distalis, Pituitary gland, Rat pups.